2020
DOI: 10.17268/sci.agropecu.2020.04.11
|View full text |Cite
|
Sign up to set email alerts
|

Defense inductors in the control of mildew (Peronospora variabilis Gaum.) in the quinoa crop: Detection, epidemiology, symptoms, characteristics and control

Abstract: Inductores de defensa en el control del mildiu (Peronospora variabilis Gaum.) en el cultivo de quinua: Detección, epidemiología, síntomas, características y control Defense inductors in the control of mildew (Peronospora variabilis Gaum.) in the quinoa crop: Detection, epidemiology, symptoms, characteristics and control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…In the case of the varieties, the AUDPC values fluctuated from 4.58 ± 0.42 to 48.58 ± 11.25 (figure 8). In general, these values represent a low level of pathogen damage when compared to the values of 2,161 (Aguilar et al, 2020) and 442 (Risco and Mattos, 2015) found in control quinoa plants.…”
Section: Presence Of Diseasesmentioning
confidence: 67%
“…In the case of the varieties, the AUDPC values fluctuated from 4.58 ± 0.42 to 48.58 ± 11.25 (figure 8). In general, these values represent a low level of pathogen damage when compared to the values of 2,161 (Aguilar et al, 2020) and 442 (Risco and Mattos, 2015) found in control quinoa plants.…”
Section: Presence Of Diseasesmentioning
confidence: 67%
“…Bio-pesticide or plant extracts could replace fungicides with a uniform and preventive application [ 5 ]. Inducers of resistance are an alternative [ 108 ].…”
Section: Downy Mildew Of Quinoamentioning
confidence: 99%
“…Other options to consider are discovering, transforming, and deploying resistant alleles existent in wild species such as C. albums [ 52 , 123 , 124 ]. Because tolerant varieties seem to delay and reduce the disease progression, inducers of resistance [ 125 , 126 ] could be a feasible option [ 108 ].…”
Section: Downy Mildew Of Quinoamentioning
confidence: 99%
“…De acordo com Del Ponte et al (2017), o desenvolvimento de dois diagramas (linear e logarítmico-HB) para auxiliar na avaliação visual da severidade do míldio em quinoa foi motivado por desenvolvimentos recentes na tecnologia do diagrama de severidade (DS), bem como pelas melhores práticas para desenvolvimento e avaliação Estatísticas. As ferramentas disponíveis para avaliar a severidade do míldio na quinoa, como as escalas de severidade propostas por Aguilar et al (2020), são geralmente pouco práticas para os avaliadores, uma vez que não têm um diagrama associado, além de possuírem muita subjetividade. Alguns diagramas de severidade propostos, como os de Danielsen et al (2001), possuem 14 níveis de severidade, o que dificulta a avaliação.…”
Section: Métodounclassified